Magnetic resonance imaging of the brachial plexus. Part 1: Anatomical considerations, magnetic resonance techniques, and non-traumatic lesions - Pawel Szaro; Alexandra McGrath; Bogdan Ciszek; Mats Geijer (European Journal of Radiology Open, 2022)
For magnetic resonance imaging (MRI) of non-traumatic brachial plexus (BP) lesions, sequences with contrast injection should be considered in the differentiation between tumors, infection, postoperative conditions, and post-radiation changes. The most common non-traumatic inflammatory BP neuropathy is radiation neuropathy. T2-weighted images may help to distinguish neoplastic infiltration showing a high signal from radiation-induced neuropathy with fibrosis presenting a low signal.MRI findings in inflammatory BP neuropathy are usually absent or discrete. Diffuse edema of the BP localized mainly in the supraclavicular part of BP, with side-to-side differences, and shoulder muscle denervation may be found on MRI.BP infection is caused by direct infiltration from septic arthritis of the shoulder joint, spondylodiscitis, or lung empyema.MRI may help to narrow down the list of differential diagnoses of tumors. The most common tumor of BP is metastasis. The most common primary tumor of BP is neurofibroma, which is visible as fusiform thickening of a nerve. In its solitary state, it may be challenging to differentiate from a schwannoma.The most common MRI finding is a neurogenic variant of thoracic outlet syndrome with an asymmetry of signal and thickness of the BP with edema. In abduction, a loss of fat directly related to the BP may be seen.Diffusion tensor imaging is a promising novel MRI sequences; however, the small diameter of the nerves contributing to the BP and susceptibility to artifacts may be challenging in obtaining sufficiently high-quality images.